Accessory Gvp Proteins Form a Complex During Gas Vesicle Formation of Haloarchaea - Völkner, Kerstin; Jost, Alisa; Pfeifer, Felicitas (Frontiers in Microbiology, 2020)
Halobacterium salinarum forms gas vesicles consisting of a protein wall surrounding a gas-filled space. The hydrophobic 8-kDa protein GvpA is the major constituent of the ribbed wall, stabilized by GvpC at the exterior surface. In addition, eight accessory Gvp proteins are involved, encoded by gvpFGHIJKLM that are co-transcribed in early stages of growth. Most of these proteins are essential, but their functions are not yet clear. Here we investigate whether GvpF through GvpM interact. Pull-down experiments performed in Haloferax volcanii with the cellulose-binding-domain as tag suggested many interactions, and most of these were supported by the split-GFP analyses. The latter study indicated that GvpL attracted all other accessory Gvp, and the related GvpF bound besides GvpL also GvpG, GvpH and GvpI. A strong interaction was found between GvpH and GvpI. GvpG showed affinity to GvpF and GvpL, whereas GvpJ, GvpK and GvpM bound GvpL only. Using GvpA for similar analyses yielded GvpF as the only interaction partner. The contact site of GvpF was confined to the N-terminal half of GvpA and subsequently mapped to certain amino acids. Taken together, our results support the idea that the accessory Gvp form a complex early in gas-vesicle assembly attracting GvpA via GvpF.